2011
DOI: 10.3892/ijo.2010.868
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of EZH2 is associated with a poor outcome and P53 alteration in squamous cell carcinoma of the esophagus

Abstract: Abstract. EZH2 and BMI1 are transcriptional repressors and have been implicated in the progression of human cancers. Squamous cell carcinoma of the esophagus (ESCC) is one of the most aggressive carcinomas in the gastrointestinal tract and generally has an unfavorable outcome. In the present study, we immunohistochemically investigated the expression of EZH2 and BMI1 in 136 surgically resected ESCCs and adjacent epithelium. We also analyzed associations between aberrant expression of EZH2 and BMI1, and both cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…Elevated EZH2 was significantly correlated with TNM stage and lymph node metastasis in CRC tissues [13]. Moreover, many works demonstrate that upregulation of EZH2 is a sign of poor prognosis [10,11,12], which indicate that EZH2 as an oncogene. However, there is disparate point of view that high level expression of EZH2 inhibits aggressive T-acute lymphoblastic leukemia [18], which means EZH2 can also act as a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated EZH2 was significantly correlated with TNM stage and lymph node metastasis in CRC tissues [13]. Moreover, many works demonstrate that upregulation of EZH2 is a sign of poor prognosis [10,11,12], which indicate that EZH2 as an oncogene. However, there is disparate point of view that high level expression of EZH2 inhibits aggressive T-acute lymphoblastic leukemia [18], which means EZH2 can also act as a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that EZH2 is associated with a number of cancers, including nasopharyngeal esophageal cancer, breast cancer, lung cancer and bladder cancer [6,7,8,9]. Moreover, overexpression of EZH2 indicates the tumor more aggressive and is related to poor prognosis [10,11,12]. In our previous immunohistochemical research, we found that expression of the EZH2 was significantly higher in tumor tissues than the paired normal tissues, and EZH2 might facilitate tumorigenesis in CRC cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Yamada et al . showed that in squamous cell carcinoma of the esophagus (SCCE), elevated EZH2 expression was associated with p53 alteration and activated p53 reduced EZH2 mRNA levels in SCCE cell lines (94). Furthermore, EZH2 was found to be a miR-144 target gene and miR-144 down-regulation in bladder cancer cells was demonstrated to restore EZH2 expression, which further resulted in the activation of Wnt/ β-Catenin pathway and subsequent cell proliferation (95).…”
Section: Role Of Ezh2 In Cancer Progressionmentioning
confidence: 99%
“…SUZ12 and EZH2 are components of the PRC2 complex responsible for the methylation of histone 3 lysines 9 and 27 (H3K9me3 and H3K27me3). Increased expression of EZH2 has been associated with poor outcome in breast cancer [3,106-110]. As mentioned above, the PcG family of proteins plays important roles in the regulation of differentiation-related genes and may be involved in the recruitment of DNMTs [111].…”
Section: Variant Human Mammary Epithelial Cells Display Cancer-associmentioning
confidence: 99%